Design of an Inverter-Based OTA Based on a 130 nm CMOS Process (Research, Society and Development, 2020)
In manufacturing processes of integrated differential amplifiers, an inherent characteristic is that the fabricated nMOS and pMOS transistors have physical differences in relation to the projected values, an effect known as mismatch. In this work, the manufacturing process variations in operational transconductance amplifiers (OTA) are evaluated. Two OTA based on CMOS inverters are designed using both low threshold and standard threshold uniformly doped transistors using quantitative experimental research.